The role of ethnic politics in promoting democratic governance: a case study of Malaysia - Shukri, Syaza Farhana Mohamad (IIUM Press, International Islamic University Malaysia, 2017)
It is a known fact that Malaysia has been ruled by a coalition of political parties demarcated along ethnic lines since independence more than 50 years ago. How has this affected democratic governance in a relatively young multi-ethnic nation? Some have argued that ethnic, religious, or linguistic politics threaten democracy as they leave room for the majority to abuse the minorities, which in turn disrupts democratic governance of a country. This paper will argue against this idea that consolidation of democracy is difficult in a heterogeneous society by using Malaysia’s leadership and institutions after independence as an example. The approach to the problem is to account for Malaysia’s relative stability and repeated experiences with elections as evidence that having multiple ethnicities do not necessarily have to lead to discord in a country, but could instead lay the foundation for democratic consolidation. This argument is appealing because the relationship between diversity and democracy is an on-going debate as racial and religious conflicts are occurring almost everywhere in the world.